Tenofovir disoproxil fumarate versus entecavir on the prognosis of hepatitis B virus-related hepatocellular carcinoma after surgical resection: a systematic review and meta-analysis - Wang, Yong; Wu, Jia-yu; Xiang, Qian; Liao, Tian-fen; Jiang, Xiao-yan; Chen, Jing (Frontiers in Oncology, 2025)
Background and aimEntecavir (ETV) and tenofovir disoproxil fumarate (TDF) are first-line antiviral treatment methods for chronic hepatitis B virus (HBV) infection. However, the different effects of TDF versus ETV on the prognosis of HBV-related hepatocellular carcinoma (HCC) after surgical resection remain controversial. We conducted this meta-analysis to assess the differences of TDF versus ETV in recurrence and survival for HBV-related HCC after liver resection.MethodsWe searched MEDLINE, EMBASE, PubMed and Web of Science for the related studies published before January 2025. Meta-analysis was performed by use of a random-effects model.ResultsA total of 15 studies were included in this meta-analysis. The pooled results showed that TDF was associated with better recurrence-free survival (RFS) (HR= 0.79, 95% CI 0.70-0.88) and lower risk of recurrence (HR=0.73, 95% CI 0.62-0.86) than ETV in HBV-related HCC patients after surgical resection. Further analysis indicated that TDF reduced the risk of late recurrence (HR= 0.70, 95% CI 0.55-0.88) rather than early recurrence (HR= 1.00, 95% CI 0.85-1.17) compared with ETV. Also, the pooled results revealed that TDF was associated with better overall survival (OS) (HR= 0.55, 95% CI 0.41-0.74) and lower risk of overall mortality (HR= 0.55, 95% CI 0.41-0.74) than ETV.ConclusionThis meta-analysis provided evidence that TDF has better benefits in improving survival and reducing late recurrence than ETV in HBV-related HCC patients after surgical resection.